Features of Transmission From Mother to Fetus During Pregnancy and Lactation (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents literature data on possible ways of infection of the fetus and newborn in the ante- and postnatal periods of development. It has been shown that the transplacental transmission of the pathogen and the infection of the fetus from the amniotic fluid can contribute not so much to the pathology of the maternal organism itself, but to the stressful situations to which the maternal organism is exposed. During the period of lactotrophic nutrition, stop breastfeeding the baby, in order to prevent infection of the baby, only for very urgent indications.